Tinjauan Historis Undang-Undang Simbur Cahaya yang Pernah Berlaku dalam Peradilan Adat di Ogan Ilir (Studi terhadap Pergaulan Bujang Gadis Dahulu dan Sekarang) - Nurmala Hak (An Nisa'a, 2018)
The views of the people in the Ogan Ilir region towards the implementation of the Simbur Cahaya Law and its contribution to the development of law today. The response of the people in the Ogan Ilir region to the Law of the Simbur Cahaya is very positive, because the Law makes the society more orderly and contains the rules that are very supportive, and uphold moral values ​​that are in line with the teachings of Islamic law. Its existence is a unity in applying the law, especially with regard to the relationship of girls, that the behavior and association of girls in the present condition may be said to have deviated from the provisions of applicable law, both state law and Islamic law. The Light Law of Simbur is the result of history, therefore with the text of this Law of Light Simbur, it can be a future reference to protect and regulate the behavior of girl friend association and apply severe sanctions to the parties who sexually harass.